Performance of single mode tapered optical fiber sensor based on localized surface plasmon resonance (LSPR) for various coating time - Musa, Nurfatin (2020)
Tapered optical fiber (TOF) sensor based on localized surface plasmon resonance is demonstrated for refractive index sensing application. The single-mode fiber (G652D) with 10/125 m of core/core-cladding diameter was tapered by flame brushing method and achieved a waist diameter of approximately 15m. Mercapto group (-SH) of 3-mercatoptopropyltrimethoxysilane (MPTMS) was utilized for immobilization of gold nanoparticles (AuNPs) by self-assemble monolayer (SAM) method on fiber surface. Evanescent field at the TOF sensing region excites the localized surface plasmons of AuNPs, with average mean diameter 15 ± 2 nm as evidence by scanning electron microscopy (SEM). The effect on deposition time was examined on three different samples; S1, S2 and S3 with 24h, 48h and 72h of coating time respectively. TOF sensor performance was evaluated with surrounding refractive indices ranges from 1.3324 to 1.4254. The sensing mechanism is based on the modulation of output light signal that represent by transmission shifting spectra. The optimum sensitivity was obtained for S2 at 18 nm/RIU with good repeatability, reversibility and stability.